Pengaruh Akuntabilitas Dan Transparansi Terhadap Kinerja Instansi Pemerintah Daerah Kota Surabaya - Desy Tri Santi Rahmadani; Maulidah Narastri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Abstract.This research aims to test the ability of Accountability and Transparency regarding the Performance of Regional Government Agencies at the Surabaya City Investment and PTSP Service. The population in this study were employees at the Surabaya City Investment and PTSP Service. The sampling techniquel in this relselarch was purposivel sampling with a total samplel of 72 relspondelnts. Collelcting relselarch data by distributing quelstionnairels to relselarch relspondelnts. Thel data analysis telchniquel useld in this relselarch is multiplel linelar relgrelssion analysis. Thel relselarch relsults found that both simultanelous and partial accountability and transparelncy had a significant positivel elffelct on thel pelrformancel of relgional govelrnmelnt agelnciels at thel Surabaya City Invelstmelnt and PTSP Delpartmelnt.